“Nothingness or a God”: Nihilism, Enlightenment, and “Natural Reason” in Friedrich Heinrich Jacobi’s Works - STEFAN-SEBASTIAN MAFTEI (Meta: Research in Hermeneutics, Phenomenology and Practical Philosophy, 2013)
Our paper analyzes one of the most important philosophical problems of the philosophies of the Enlightenment: the problem of the emergence and the justification of the autonomy of reason. Our study will reflect on the critique of the autonomous reason, a critique brought by the Enlightenment thinkers themselves. Kant is one example of criticizing, and moreover securing the status of reason in the Enlightenment. Friedrich Heinrich Jacobi, however, was not only an adversary of transcendental philosophy, but also a radical critic of the concept of ‘reason.’ In Jacobi’s works, reason faced a powerful critique of its own mechanisms of justification. Jacobi’s main thesis is that reason is threatened by the prospect of nihilism lurking from inside its main body of axioms. His critique against nihilism from the point of view of a believer is nothing new to the history of ideas, but here the direction of the critique changes against the vein of the Modern Age’s mainstream views with respect to the relation between reason and faith: reason’s own standards of truth are deemed as incapable of securing a safe place for reason against the prospect of an overwhelming nihilism. Thus, Jacobi emphasizes again and again that reason or cognition must find its standard of truth outside itself, or else it must face the scene of nothingness.